Labour skills and cultural competence in the hotel sector in peru: insights from frontline employees - Gelacio-Macedo, Katty Antonela (2025)
This study explores the job competencies required of front-line employees in four-star hotels in Lima, Peru, situating these skills within the cultural dynamics of hospitality work. In global tourism contexts, hotel service involves not only operational efficiency, but also the fulfilment of social expectations, emotional management and the demonstration of culturally appropriate behaviours. Through a qualitative approach, based on in-depth interviews with human resource managers, the research analyses the knowledge, skills, attitudes and experiences that define effective performance in hotel operations. The results show that employees must possess not only technical knowledge, but also key interpersonal competencies such as advanced English proficiency, teamwork, autonomy, leadership and adaptability. Likewise, knowledge associated with the use of hotel technologies, management systems, customer service and conflict resolution are identified as relevant. These competencies are not only functional, but also represent expressions of internalised cultural values, such as empathy, charisma and service-mindedness, which shape the symbolic relationships between employees and guests. The research shows that structural changes following the pandemic have reshaped job profiles, requiring greater versatility, role rotation and flexible planning. These transformations reinforce the need for culturally sensitive competencies, able to adjust to global institutional standards and local interaction practices. In this sense, the training of workers acquires a double dimension: technical and symbolic, where service not only satisfies functional needs, but also cultural expectations deeply rooted in the tourist experience. In conclusion, this study contributes to cultural studies applied to tourism by showing that labour competencies in the urban hotel sector not only respond to organisational demands, but also act as vehicles of cultural significance. The work of contact employees becomes a form of symbolic mediation that transmits values, norms and aesthetics of local service in internationalised contexts. The findings offer strategic orientations for human talent management and open up lines of future research on the crossover between labour competencies and cultural representations in the tourism industry.